An Electrochemical Aspect On Pressure Precipitation Of Nickel - Tadao Nagai; Masao Sato (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1973)
Electrochemical measurements have been carried out in an auto- clave to investigate the electrochemistry of hydrogen precipitation of nickel from acetate buffered solution. After having previously obtained the rate equation for this reaction we have now made a concentrated effort to explain the rate equation electrochemically. A saturated NaC1-type Ag/AgC1 reference electrode has been improved so that it can be used in an autoclave. Polarization curves for the reaction, [H2=2H+ + 2e,] on nickel electrode were measured in solutions free from nickel ions at 185°C, and the parallel curves were obtained by changing PH2 and pH for normal and reverse reactions, respectively. Polarization curves in nickel solutions were complex, probably because the potential of hydrogen electrode is close to that of nickel and of the nickel surface altered during polarization. Then the nickel electrode potential and the reaction rate were measured simultaneously during pressure reduction at various hydrogen pressures and at various nickel concentrations. The reaction rates in terms of current density were plotted to obtain the local polarization curves for reactions Ni2+ + 2e ? Ni and H2 ?2H+ + 2e. The anodic and cathodic local polarization curves exhibit potential dependency. Therefore it is likely that the pres- sure reduction can be regarded as a coupled electrodes reaction.